Chewing khat and risky sexual behavior among residents of Bahir Dar City administration, Northwest Ethiopia - Andargie Abate; Minale Tareke; Mulat Tirfie; Ayele Semachew; Desalegne Amare; Emiru Ayalew (Annals of General Psychiatry, 2018)
Abstract Introduction Khat is a well-known natural stimulant and is widely used in Ethiopia, particularly in Bahir Dar city. Khat chewing is linked with risky sexual behaviors. Objective The study was aimed to determine the prevalence of chewing khat and its relation with risky sexual behaviors among residents of Bahir Dar City administration, Northwest Ethiopia. Methods A community based cross-sectional study was conducted from January to February, 2016. The data were collected using an interviewer administered structured questionnaire. Logistic regression analysis was applied to assess association between dependent and explanatory variables. Results The proportion of lifetime and current chewing khat among the study participants were 25.7 and 19.5%, respectively. Males (AOR 5.0; 95% CI 3.0–8.2) than females, merchants (AOR 4.9; 95% CI 2.6–9.3) than government employees, and those with average monthly income of ≥ 3001 Ethiopian birr (AOR 2.4; 95% CI 1.2–4.8) than ≤ 1000 had an increased current chewing khat prevalence. Having lifetime history of chewing khat was significantly associated with ever had sexual intercourse, having extra sexual partners, watching pornographic film and self-reported sexually transmitted infections. Conclusion Chewing khat is associated with increment of having risky sexual behaviors and self-reported sexually transmitted infections. Harm reduction measures are needed to prevent the community from engaging in khat use and risky sexual behaviors.